Investigation on the functional requirements for talent management system – a case of performing arts freelancers in Malaysia - Bahar, Nurhidayah; Subaramaniam, Kasthuri; Masoud, Adnan; Shibghatullah, Abdul Samad; Abd Wahab, Mohd Helmy (Springer, 2022)
This study examines job seeking and hiring process between freelancers and agency or event organizer in performing arts industry in Malaysia. The main aim of this study is to develop a set of system functional requirements for Talent Management System – a job portal that can be used to automate and computerized job seeking and hiring process. To achieve the aim, the study employed a qualitative research approach and followed an object-oriented analysis and design with the Unified Process methodology. A total of 10 interviews were conducted with freelancers, agencies, and organizers to gain an in-depth understanding of the process, constraints, and concerns about the current practice. The finding from this study highlighted the important system’s functions and provides guidelines on the system design and implementation. Hence, it offers some insights to the system developers who will be working on a similar system. Additionally, this study adds some knowledge to the literature related to talent management system and performing arts. Future studies may want to further design the data access layer, system interfaces, controls, and security.